Batik Buketan Motif Bunga Nasional Indonesia Dan Penerapannya Dalam Busana Bernuansa Vintage - Budiarti Nafisah; Esther Mayliana; I Made Sukanadi (Institut Seni Indonesia Padangpanjang, 2021)
National flowers are considered to represent the character of the nation and state. The flowers chosen as the national flower of Indonesia are white jasmine, moon orchid, and raflesia arnoldi. Floral motifs have often been used as a source of ideas for making batik since ancient times, one of which is the Bouquetan batik motif which was popularized by Dutch women at that time. classic style.The author makes four collections of works entitled